The Relationship Between Flag Leaf Senescence and Grain Yield of - Murat Tiryakioğlu (Journal of Agricultural Sciences)
This study aimed at investigating genotypic differences in the leaf area duration of durum wheat genotypes during grain filling periods and their relation to grain yield under two different irrigation conditions. The experiments were designed randomized complete block design for four replication in 2009/2010 and 2010/2011. Irrigation levels in main plots, cultivars were included in the sub plots. The study gathered data of six genotypes with similar anthesis times in Antakya/Hatay-Turkey. During the growth period, the two groups of plants received general management techniques and 60 kg ha-1 phosphorus and 80 kg ha-1 nitrogen (ammonium sulphate) fertilizer. Two different irrigation regimes were applied; the control group received full irrigation until reaching physiological maturity, while the experiment group was not irrigated after anthesis but instead received rainfall characteristic of WANA (West Asia North Africa). Results showed that flag leaf area (FLA) and lower leaf area (LLA) were not significantly related to spike grain yield (SGY) under control conditions. Flag leaf area duration (FLAD) was not related to grain yield, while the increase in lower leaf area duration (LLAD) reduced grain yield. Meanwhile, a positive relation was observed between FLA and SGY under experimental conditions, since SGY significantly increased according to the increase of FLAD. Moreover, high FLAD positively contributed to grain filling under both the conditions, while high LLAD partly contributed only under control conditions. These results suggest that the genotypes with low leaf number or short plant height and low tillering capacity should receive significant irrigation, while genotypes with middling plant height should be planted during conditions of drought stress. Under both the sets of conditions genotypes must have high FLAD.